Pengembangan Media Komik Petualangan Wong Banten untuk Kelas IV Sekolah Dasar di Cilegon - Mafdurotul Goliah; Aan Hendrayana; Suroso Mukti Leksono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The erosion of regional languages is a problem that needs to be addressed by all groups, including families, educational institutions and the government. One of the ways the government has taken to overcome the erosion of the Cilegon Javanese language is by requiring the learning of Nalek (Cilegon Javanese) in elementary schools, but in fact the implementation of learning has not been optimal due to the lack of supporting media that can be used in Nalek learning. The aim of this research to develop the Wong Banten adventure comic media to increase literacy in Cilegon Javanese for class IV elementary schools in Cilegon. The research method used is the development research method with the ADDIE model which has five stages: Analysis, Design, Development, Implementation, and Evaluate. The data collection techniques and methods used in this research were interviews and questionnaires, while the data analysis used used descriptive qualitative and quantitative. The results of this development research were that the feasibility score from material experts was 98.64% in the very good category, media experts were 85% in the good category, language experts were 94.28% in the very good category, and student questionnaire responses were 79%. with good category. Based on these results, the Wong Banten adventure comic media can be said to be suitable for use by students in class IV elementary school Nalek learning in Cilegon. It is hope that the result of development of the Wong Banten adventure comic media can be disseminated and used as a medium for learning Cilegon Javanese in Cilegon.